Efek suplementasi vitamin A pada ibu nifas terhadap pertumbuhan bayi umur 0-4 bulan - Abdullah Abdullah; Endy Paryanto Prawirohartono; Siti Helmyati (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2013)
Background: Vitamin A deficiency is a nutritional problem in infants since breastmilk insufficiently contains vitamin A. Therefore it is necessary to study the effect of vitamin A supplementation to mothers at parturition period on growth and morbidities of infants at 0-4 months of age.Objective: To identify the effect of vitamin A supplementation to mothers at parturition period on growth and morbidities of infants at 0-4 months of age.Method: We conducted a randomized controlled trial from March-July 2009 at Province of Lampung. We recruited 90 mothers that were grouped into vitamin A supplementation group and socialization about vitamin A group during parturition period. The outcomes of this study were growth in WHZ and morbidities of infants at 0-4 months of age measured as duration of acute diarrhea and upper respiratory infections. Statistical analysis was performed by using Chi-Square and t-test.Results: The growth of infants of 0-4 months from vitamin A supplemented mothers was not significantly different from the socialization group. Duration of diarrhea and acute respiratory tract infection of infants from supplemented mothers at parturition period was significantly shorter than of infants from socialization group.Conclusion: The growth of infant at 0-4 months of age from vitamin A supplemented mothers at parturition period were not significantly different from those who were from education group. Duration of diarrhea and acute respiratory tract infection of infants from vitamin A supplemented mothers at parturition period were shorter than those who were from education group.